Digitalization as a development factor of innovative-active university - Ponomarenko, Volodymir; Rayevnyeva, Olena; Yermachenko, Volodymyr; Aksonova, Iryna; Brovko, Olha (LLC "СPС "Business Perspectives", 2021)
A characteristic feature of the XXI century is the emergence of the digital society phenomenon, which significantly changes all processes in higher education. The implementation of innovations into university activity, creation of its digital culture, and digital environment are the key features of an innovative-active university (IAU) and factors of its development. The paper aims to develop a strategy and innovative-indicative measures for digitalization of IAU activities based on the study of society’s digital maturity. Index, rating, comparative analyzes, and decomposition method were used. It is determined that Ukraine has a significant gap in comparison with the developed countries in terms of digital maturity of society and occupies lower than average positions in international informatization indices. To assess the state of digitalization processes in Ukraine, government measures for the development of digital culture were analyzed, the limitations and triggers of society digitalization are identified. It is proved that the digitalization of education has a dominant impact on the overall level of digital competitiveness. That is, the introduction of information and communication technologies in the IAU activity is an urgent task of its management. The digitalization strategy of S.Kuznets KhNUE in accordance with its educational, scientific and technical, marketing, and international activities was created. The proposed strategy is based on a systemic understanding of digitalization processes, which makes it possible to increase the degree of their controllability. A set of innovative and indicative measures was developed, which constitute the tactical contour of IAU digital process management.
Keywords: university activity; digital culture; digitalization strategy; innovative and indicative measures